KEPEMIMPINAN LURAH DALAM PENGELOLAAN BANK SAMPAH DI KELURAHAN RAYA KECAMATAN SINGKEP BARAT KABUPATEN LINGGA PROVINSI KEPULAUAN RIAU - Agung Nurrahman; Gatiningsih Gatiningsih; Muhammad Tri Syaputra (Program Studi Manajemen Keamanan dan Keselamatan Publik IPDN, 2021)
This research focuses on how leadership has a major role in addressing environmental issues, especially through the garbage bank program as a form of case study. Furthermore, the problems that occur in the midst of society are often rely solely on political will or political desire to solve them. The research is to know and learn Lurah's (head of village) leadership in the management of waste banks specifically. This research is qualitative descriptive research. Data collection techniques through structured interviews, documentation and observations. Researchers conducted an analysis using leadership theory from Yukl, where the theory discusses leadership comprehensively. Researchers only focus on five parts of the concept that are considered relevant, namely: visionary, guidance, affiliative, democratic and communicative concepts. The results of this study based on these dimensions are good enough Lurah (head of village) leadership. But there are several things that are considered able to optimize the running of the program through the role of Lurah (Head of village) leadership, namely: first, involving active knots and community leaders such as MUI, academics to support scientific aspects, and professionals in the field of practical management. Keywords: Leadership, Head of Village, Environmental Issues, Waste Management, Waste Bank